(untitled) (Research, Society and Development, 2022)
Biodiesel is considered a clean and renewable energy source, however it is important to know the environmental impacts caused by the water-soluble fraction (WSF) of this fuel, in the event of a spill. The objective of this research was to evaluate the seawater-soluble fraction of biodiesel (B100) compared to diesel (S500). A factorial design was used to carry out the experiments and evaluate the WSF’s, varying the type of fuel and the contact time between oil and water (O/W) from 1h to 24h. The mortality rate (%) of Mysidopsis juniae and the concentration of total hydrocarbons (TPH) were used as response variables. The results obtained demonstrate that diesel showed greater toxicity, with an average mortality rate of 98.4 % and TPH concentration of 475.8 µg/L in the water-soluble fraction. On the other hand, biodiesel did not present significant toxicity in the exposure of organisms, even after 24 hours of contact, but it can still cause risks in cases of spillage (average mortality rate of 15.0%). The empirical models obtained using the experimental design methodology were able to satisfactorily estimate the TPH concentrations and the mortality rate in the WSF, with precision above 99%, with correlation coefficients (R²) of 0.9963 and 0.9970. Pure biodiesel, due to its low lethality of organisms, biodegradable and from a renewable source, is an ecologically favorable proposal as a fuel, causing less impacts in cases of spillage in seawater.